Estimation of Differences in Work Attitudes by National Character from Psychological Change Points - Matsuno, Koki; Shimakawa, Hiromitsu (Advances in Social Sciences Research Journal, 2024)
More and more foreign workers work in Japan year by year. However, there is a problem that a few foreign workers keep working in Japan. One of the reasons is the work attitudes of foreign workers is different from those of Japanese companies. Japanese companies want to fully understand their work attitudes so that they can develop foreign workers’ human resources appropriately. This study proposes a method for estimating the differences in the work attitudes from physiological characteristics during video watching. The method uses videos to collect psychological change points during the viewing. Pupil diameter is measured to estimate cognitive change while EDA is measured to estimate emotional change. Change points are detected from time series of the physiological characteristics to know the scene causing the changes. The work attitudes are also examined from questionnaires. An experiment reveals differences in cognitive change indicating that Japanese and Vietnamese have different views on work. It also showed that Japanese and Vietnamese have different attitudes towards work difficulties and responsibilities. Differences in emotional change indicated that Japanese and Vietnamese differ in the factors that cause emotional change. The findings can be used for human resource development to assign suitable work to foreign workers.